Longitudinal Guidance of Unmanned Aerial Vehicle Using Integral Sliding Mode Control. (2016) - Haridas, Varsha; Vivek, A.
Abstract: This paper proposes a nonlinear scheme for guidance and longitudinal control of Unmanned Aerial Vehicle(UAV). The main objective of the guidance algorithm is to minimize the errors in altitude and flight path angle of the vehicle during flight. The guidance scheme must perform well in the case of small as well as large longitudinal errors, without saturating the pitch angle of the vehicle, which act as the control input. Integral Sliding Mode Control(ISMC) is used in longitudinal control of UAV. It is an improved sliding control method. Initially a linear sliding surface is employed for longitudinal guidance but it cannot provide satisfactory performance for both large and small errors in altitude and flight path angle and hence a nonlinear sliding surface is proposed. The simulations are carried out in MATLAB ® /SIMULINK ® .The simulation results show the effectiveness and robustness of the proposed control scheme.